Avaliação radiográfica de fêmur e tíbia em cães da raça spitz alemão com luxação patelar medial - Machado, Mariana Corneglian de Carvalho (2023)
The purpose of the study was to measure radiographically the femoral and tibial angles of Pomeraian dogs with grade I to III medial patellar luxation (MPL). 35 pelvic limbs were evaluated and classified into three groups: grade I, grade II and grade III of MPL. The images were obtained through standardized radiographs under anesthesia. The values of the angles were measured on craniocaudal radiographic images of femurs and caudocranial and mediolateral of tibias. The angles determined were: anatomical lateral proximal femoral angle (aLPFA), anatomical lateral distal femoral angle (aLDFA), mechanical lateral proximal femoral angle (mLPFA), mechanical lateral distal femoral angle (mLDFA), inclination angle (ICA), femoral varus angle ( FVA), mechanical medial proximal tibial angle (mMPTA), mechanical medial distal tibial angle (mMDTA), mechanical cranial proximal tibial angle (mCrPTA), mechanical cranial distal tibial angle (mCrDTA) and tibial plateau angle (TPA). No significant difference (p > 0.05) was observed in the values obtained for ICA, FVA and aLDFA. Means of mLPFA were significantly higher as the grade of PML increased. Significant differences were not observed in tibial angles measurements. Therefore, the results warrant further investigations of femoral and tibial angles in Pomeranian dogs with and without MPL and also the comparison with measurements obtained through computed tomography images.